Primary bone tumors: value of MR angiography for preoperative planning and monitoring response to chemotherapy - Lang, P; Grampp, S; Vahlensieck, M; Johnston, JO; Honda, G; Rosenau, W; Matthay, KK; Peterfy, C; Higgins, CB; Genant, HK (American journal of roentgenology (1976), 1995)
The purposes of our study were to investigate the use of MR angiography with two- (2D) and three-dimensional (3D) displays in evaluating vascular morphology of musculoskeletal neoplasms for preoperative planning of limb-salvage surgery and to assess the use of MR angiography for monitoring changes in neovascularity and evaluating response to chemotherapy. We used MR angiography (2D time-of-flight) to study 13 patients with primary bone tumors (nine osteogenic sarcomas, two Ewing's sarcomas, and two primary lymphomas of bone) at the time of initial presentation. Eight patients (all of whom had osteogenic sarcoma) also underwent MR angiography following chemotherapy before limb-salvage surgery. Two-dimensional maximum intensity projections were obtained. Three-dimensional reconstructions of vascular structures were created from the angiographic source images and were displayed simultaneously with 3D reconstructions of tumor and normal bone generated from conventional MR images. Two-dimensional maximum intensity projections were useful for evaluating small vessel neovascularity; 3D displays demonstrated spatial relationships of tumor, feeder vessels, and normal vascular structures. Tumor encroachment onto or encasement of normal vascular structures was shown in four patients on 2D maximum intensity projections and on 3D displays. The eight patients with osteogenic sarcoma who had follow-up imaging showed marked neovascularity prior to chemotherapy. Five patients responded to chemotherapy (> or = 90% tumor necrosis at histology); MR angiography showed marked reduction in tumor neovascularity in these patients. Three patients did not respond to chemotherapy; MR angiography showed unchanged neovascularity in one and increased neovascularity in two of these patients. MR angiography provides good visualization of peripheral vascular branches and tumor neovascularity in patients with primary bone tumors. MR angiography demonstrates encroachment onto and encasement of major vessels by the tumor mass and appears to be useful for assessing response to chemotherapy in osteogenic sarcoma and possibly other primary bone tumors by detecting treatment-induced changes in tumor neovascularity.